Body composition and nutritional intake of HIV exposed preterm, very- and extremely-low birth weight infants in Tygerberg hospital, Western Cape - Strydom, Klara (Stellenbosch : Stellenbosch University, 2018)
Thesis (MNutr)--Stellenbosch University, 2018.